The benefit of quality control charts (QCC) for routine quantitative BCR-ABL1 monitoring in chronic myeloid leukemia - Spiess, Birgit; Naumann, Nicole; Galuschek, Norbert; Rinaldetti, Sébastien; Kossak-Roth, Ute; Felde, Elena; Fabarius, Alice; Hofmann, Wolf-Karsten; Saußele, Susanne; Seifarth, Wolfgang (PLOS ONE, 2018)
Quantitative real-time polymerase chain reaction (qRT-PCR) is state of the art in molecular monitoring of minimal residual disease in chronic myeloid leukemia (CML). In this context, maintenance of assay fidelity and detection of technical inaccuracy are crucial. Beside multiple common negative controls for the clinical sample preparations, quality control charts (QCC) are a common validation tool to sustain high process quality by continuously recording of qRT-PCR control parameters. Here, we report on establishment and benefit of QCC in qRT-PCR-based CML diagnostics. The absolute quantification of BCR-ABL1 fusion transcripts in patient samples is based on coamplification of a serially diluted reference plasmid (pME-2). For QCC establishment the measured Ct values of each pME-2 standard dilution (4-400,000) of a test set resembling 21 sequential qRT-PCR experiments were recorded and statistically evaluated. Test set data were used for determination of warning limits (mean +/- 2-fold standard deviation) and control (intervention) limits (mean +/- 3-fold standard deviation) to allow rapid detection of defined out-of-control situations which may require intervention. We have retrospectively analyzed QCC data of 282 sequential qRT-PCR experiments (564 reactions). Data evaluation using QCCs revealed three out-of-control situations that required intervention like experiment repeats, renewal of pME-2 standards, replacement of reagents or personnel re-training. In conclusion, with minimal more effort and hands-on time QCC rank among the best tools to grant high quality and reproducibility in CML routine molecular diagnosis.